H8 Filtering for Uncertain Periodic Markov Jump Systems with Periodic and Partly Unknown Information - Zhu, L.; Yin, YanYan; Liu, F.; Wang, Song (Birkhauser, 2018)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature. This paper studies the problem of H8 filtering for a class of uncertain discrete-time periodic Markov jump systems with partly unknown and periodic transition probabilities, which is described as a polytope. By using Lyapunov function, periodic H8 filter is designed, which ensures that the periodic dynamic system is stochastically stable and satisfies a prescribed H8 performance index. A numerical example is presented to illustrate the effectiveness of the proposed theoretical results.